Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 216710 species occurrences available in GBIF matching the query: { "and" : [ "HasGeospatialIssue is false", "Geometry POLYGON((-100.31 20.73,-100.31 21.76,-98.59 21.76,-98.59 20.73,-100.31 20.73))" ] } The dataset includes 216710 records from 390 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0085295-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences